Discussies over zes eeuwen waterbeheer en samenleving: Repliek - van Tielhof, Milja (TSEG - The Low Countries Journal of Social and Economic History, 2023)
In this response, I would like to respond to the main issues they raised. the nature of the widespread participation of the peasantry in the large-scale water systems that were established in the Middle Ages; the commons, a major reorganization of management of waterworks that runs as a thread through six centuries of Dutch water management; new questions concerning ideology, political culture, everyday practices and material culture; and, finally, Dutch water management in an international perspective.